CASE STUDIES OF SUCCESSFUL COMPANIES USING ANALYTICS FOR GROWTH (International Conference on Medical Science, Medicine and Public Health, 2025)
In the digital age, data analytics has become a key growth driver for businesses. This study presents case studies of successful applications of analytics in companies such as Amazon, Netflix, Zara and UzAuto Motors. The case studies demonstrate how analytical tools help companies improve internal processes, enhance customer service, predict demand and make informed strategic decisions. Considerable attention is paid to the impact of business analytics on improving efficiency and competitiveness in both the international and national arenas. It is concluded that organisations that have integrated analytics into their business strategy show more stable growth and better adaptability to market dynamics.